2018
DOI: 10.1002/2017ja024796
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the Electron Fluxes in the Terrestrial Radiation Belts Due To the Impact of Corotating Interaction Regions and Interplanetary Coronal Mass Ejections

Abstract: In this paper, we study the variations of the radiation belts electron fluxes induced by the interaction of two types of solar wind structures with the Earth magnetosphere: the corotating interaction regions and the interplanetary coronal mass ejections. We use a statistical method based on the comparison of the preevent and postevent fluxes. Applied to the National Oceanic and Atmospheric Administration‐Polar Operational Environmental Satellites data, this gives us the opportunity to extend previous studies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Kellerman et al, 2015). In the recovery phase of a storm low-intensity chorus waves are also observed at all MLTs (Bingham et al, 2019) that could contribute to precipitation and enhanced CNA, in particularly for the ejecta that have more symmetric ring current than sheaths (e.g. Pulkkinen et al, 2007).…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Kellerman et al, 2015). In the recovery phase of a storm low-intensity chorus waves are also observed at all MLTs (Bingham et al, 2019) that could contribute to precipitation and enhanced CNA, in particularly for the ejecta that have more symmetric ring current than sheaths (e.g. Pulkkinen et al, 2007).…”
Section: Summary and Discussionmentioning
confidence: 96%
“…High‐speed streams are spatial structures which map to coronal holes at the Sun, regions of open magnetic flux and expanding plasma which appear dark in solar images of the plasma cooling as it expands outward. Both types of structure, which drive geomagnetic activity and variations in outer zone electron flux (e.g., Baker et al, 2019; Benacquista et al, 2018; Borovsky & Denton, 2006; Hudson et al, 2008; Kilpua et al, 2015; Reeves et al, 2003; Turner et al, 2019; Yuan & Zong, 2012), are shown in Figure 5, along with recurring enhancement in radiation belt electron flux at the solar rotation period measured at geosynchronous orbit (Reeves, 1998).…”
Section: Introduction To Van Allen Radiation Beltsmentioning
confidence: 99%
“…Using the National Oceanic and Atmospheric Administration‐Polar Operational Environmental Satellites data, Benacquista et al. (2018) have studied the flux variations for the four different energy ranges of 30, 100, 300 keV, and 1 MeV electrons in the Earth's outer rational belt due to the impact of corotating interaction regions (CIRs) and interplanetary coronal mass ejections. They found that the intensity of magnetic storms could affect not only the minimum value of L ∗ but also the flux variation of the seed electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al (2017) have statistically studied the relationship between the distribution of 336 keV electrons at L ∼ 3-5 after storms and geomagnetic indices and solar wind parameters, and they have found that geomagnetic storms and substorms play important roles in the seed population dynamics in the outer radiation belt. Using the National Oceanic and Atmospheric Administration-Polar Operational Environmental Satellites data, Benacquista et al (2018) have studied the flux variations for the four different energy ranges of 30, 100, 300 keV, and 1 MeV electrons in the Earth's outer rational belt due to the impact of corotating interaction regions (CIRs) and interplanetary coronal mass ejections. They found that the intensity of magnetic storms could affect not only the minimum value of L * but also the flux variation of the seed electrons.…”
mentioning
confidence: 99%